Monitoring of short-term erythropoietin therapy in rats with acute spinal cord injury using manganese-enhanced Magnetic Resonance Imaging - Freitag, Martin T.; Parzer, Peter; Stieltjes, Bram (Journal of neuroimaging, 2015)
BACKGROUND AND PURPOSE To evaluate the short-term outcome of erythropoietin (EPO) therapy in rats with spinal cord injury (SCI) using manganese-enhanced magnetic resonance imaging (MEMRI). METHODS Rats were divided in an EPO and a control group. Laminectomy at Th11 was performed, followed by SCI. MnCl2 was applied into the cisterna magna and functional recovery was examined after injury using BBB-scoring. Then, rats were euthanized and the spinal cord was extracted for MEMRI. Finally, histological analysis was performed and correlated with MEMRI. RESULTS EPO-treated animals showed significantly better functional recovery (P = .008, r = .62) and higher mean signal-to-noise ratio (SNR) in MEMRI compared to controls for slices 10-13 (P = .017, R2 = .31) at the level of the lesion epicenter. Functional recovery correlated significantly with higher SNR values, determined using the mean SNR between slices 10 and 13 (P = .047, R2 = .36). In this region, histology revealed a significantly decreased number of microglia cells and apoptosis in EPO-treated animals. CONCLUSION MEMRI successfully depicts the therapeutic effect of EPO in early SCI that leads to a significant recovery in rats, a significantly reduced immune response and significantly reduced number of apoptotic cells at the height of the lesion epicenter.
First published: 16 December 2014
Gesehen am 26.06.20